Diagnosis of Tailgut Cyst in Gynecologic Patients: Systematic Review of the Literature. Issue 3 (July 2017) - Schwarzman, Polina; Mastrolia, Salvatore Andrea; Sciaky-Tamir, Yael; Baron, Joel; Sheizaf, Boaz; Trojano, Giuseppe; Hershkovitz, Reli
Tailgut cysts, also called retrorectal cystic hamartomas, are rare findings that usually occur in the retrorectal space. The incidence is estimated to be about 1 in 40, 000. The aim of our review is to evaluate the potential pitfalls in the diagnosis of this rare pathologic condition, according to diagnostic procedures for this rare but misleading and subtle entity. We conducted a Medline literature review of the English literature discussing tailgut cysts in female patients. We concentrated on imaging technology used for diagnosis in gynecologic patients. For our search, we used the key words "tailgut cyst", "retrorectal cystic hamartoma", "gynecology", focusing on clinical presentation, imaging technology used for diagnosis, presence of malignancy, and misdiagnosis with more common gynecologic pathology. Our search revealed 143 articles during the years 1975–2016 and, of these, 30 articles describing 91 female patients were considered. We concluded that tailgut cyst should be included in the differential diagnosis of pelvic lesions in gynecologic patients.